Gas chromatography coupled to atmospheric pressure ionization mass spectrometry (GC-API-MS): Review - Li, Du-Xin; Gan, Lin; Bronja, Amela; Schmitz, Oliver J. (Analytica chimica acta, 2015)
Although the coupling of GC/MS with atmospheric pressure ionization (API) has been reported in 1970s, the interest in coupling GC with atmospheric pressure ion source was expanded in the last decade. The demand of a “soft” ion source for preserving highly diagnostic molecular ion is desirable, as compared to the “hard” ionization technique such as electron ionization (EI) in traditional GC/MS, which fragments the molecule in an extensive way. These API sources include atmospheric pressure chemical ionization (APCI), atmospheric pressure photoionization (APPI), atmospheric pressure laser ionization (APLI), electrospray ionization (ESI) and low temperature plasma (LTP). This review discusses the advantages and drawbacks of this analytical platform. After an introduction in atmospheric pressure ionization the review gives an overview about the history and explains the mechanisms of various atmospheric pressure ionization techniques used in combination with GC such as APCI, APPI, APLI, ESI and LTP. Also new developments made in ion source geometry, ion source miniaturization and multipurpose ion source constructions are discussed and a comparison between GC-FID, GC-EI-MS and GC-API-MS shows the advantages and drawbacks of these techniques. The review ends with an overview of applications realized with GC-API-MS. [Display omitted] •Atmospheric pressure ion sources (APCI, ESI, APPI, APLC etc) enable the coupling of LC-based high-end MS to GC.•APIs show advantages in selectivity and sensitivity compared with EI in GC-MS.•Accurate mass database in GC-APCI/MS is emerging as an alternative to GC-EI/MS database.